Merkel Cell Carcinoma of the Head and Neck. Issue 6 (June 2015) - Dawe, Nicholas; Sainsbury, David; Veeramani, Siva; Ragbir, Maniram; Ahmed, Omar A.
<x xml:space="preserve">Abstract</x> Objective Merkel cell carcinoma (MCC) is a rare, aggressive skin tumor. Controversies regarding optimal management persist due to inadequate data and knowledge regarding tumor biology. Head and neck MCC increases both oncological and reconstructive challenges, compounded by predominantly elderly patients. We review our practice and outcomes, review evidence, and discuss the difficulties in delivering best practice management. Methods All patients with primary head and neck MCC, managed by a single multidisciplinary team between January 2001 and December 2010, were identified through retrospective analysis of a pathology coding database. A literature review was performed. Results Twenty patients, with a mean age of 83.5 years (40–99 years) and presenting with mean symptom duration of 5 months, had primary tumors involving the nose (n = 2), periorbital region (n = 5), cheek (n = 6), and the temple and scalp (n = 7). Mean tumor size was 2.1 cm (range, 0.5–7.5 cm). Reconstructive techniques were direct closure (n = 8), skin grafting (n = 7), local flaps (n = 4), and free anterolateral thigh flap (n = 1). Two (10%) patients presented with nodal disease. Eight (40%) patients re-presented with nodal recurrence at a mean of 7 months with 6 undergoing salvage neck dissections. Adjuvant radiotherapy was completed in 5 cases, and chemotherapy used for palliation in 1 case. Most of the patients declined radiotherapy due to adverse effects or frailty. Conclusions Our series demonstrates the profound challenges in managing head and neck MCC, including tailoring definitive primary treatment and current consensus management to elderly patients. Regional nodal assessment and management remains crucial to achieving this goal.